Analysis of road traffic crashes as a result of human factors on South Africa’s national route 3 (N3) - Ximba, Londeka (Stellenbosch : Stellenbosch University, 2025)
Ximba, L. 2025. Analysis of Road Traffic Crashes as a Result of Human Factors on South Africa’s National Route 3 (N3). Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/68e5c841-207a-4cf3-b01c-8dda0d247697